A triple tandem columns extraction chromatography method for isolation of highly purified neodymium prior to 143Nd/144Nd and 142Nd/144Nd isotope ratios determinations. Issue 2 (21st December 2018) - Pin, Christian; Gannoun, Abdelmouhcine
Abstract : A new separation scheme is presented for the isolation of Nd fractions highly purified from adjacent lanthanides, especially Ce and Pr, in preparation to demanding isotope ratios applications, e.g. determination of 142 Nd/ 144 Nd, or measurement of 143 Nd/ 144 Nd on very small samples by using NdO + ion beams. Abstract : A new separation scheme is presented for the isolation of Nd fractions highly purified from adjacent lanthanides, especially Ce and Pr, in preparation to demanding isotope ratios applications, e.g. determination of 142 Nd/ 144 Nd, or measurement of 143 Nd/ 144 Nd on very small samples by using NdO + ion beams. Following sample dissolution with hydrofluoric and nitric acids, the method avoids lengthy evaporations, and does not require an oxidation stage to get rid of most of Ce as Ce(iv ). The scheme is based on the concatenation of several small extraction chromatographic (EXC) columns filled with three different, commercially available resins, and used in successive tandem configurations, without intervening evaporation step. In the first column, filled with 0.25 ml of the well established TRU-resin, the LREE are separated from matrix elements, and directly stripped onto a second 1 ml column filled with an HEH[HEP]-based EXC material (LN2-resin), which performs an early separation of Nd from most of Ce and Pr, and from all Sm and heavier lanthanides. The Nd fraction separated in this way is eluted on-line onto a third column filled with 1 ml of resin based on a diglycolamide extracting agent (DGA-resin), for further removal of Ce and Pr impurities. Finally, the Nd fraction is stripped from the DGA column onto the previously used LN2 column for a second pass achieving an additional "skimming" of residual Ce and Pr. The LN2–DGA tandem column cycle can be repeated as many times as desired, thereby providing Nd in an extremely pure form.